Loyalitas dan Kepuasan Penumpang pada Mass Rapid Transit - Nurul Hidayati; Masjraul Hidayat; Marthaleina Ruminda; Lira Agusinta; Prasadja Ricardianto (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2021)
The main objective of this research is to increase the loyalty of MRT Jakarta passengers in purchasing tickets through the MRT-J webquel. One of the main problems, the Load Factor of Jakarta's Mass Rapid Transit is still low, which is in the range of 15-18%, far from the standard of public transportation, which is 70%. The location of the study was carried out at Lebak Bulus Station-Hotel Indonesia (HI) Roundabout Station, with a total sample of 112 respondents with questionnaires. Processing technique with quantitative approach method using path analysis processing. The results of the study showed that service quality had a positive effect on satisfaction, webquel had a positive effect on satisfaction, service quality had a non-significant positive effect on loyalty, webquel had an influence on loyalty, satisfaction had an effect on loyalty, passenger satisfaction was unable to function as a mediation on service quality, Passenger satisfaction is able to function as a webquel mediation to passenger loyalty. To improve the quality of service by generating passenger satisfaction, special policies are needed that can make and support changes in managerial quality by providing opportunities for passengers to express their complaints, so that the company PT. Mass Rapid Transit (MRT) Jakarta can form a complaint and suggestion system.